Physiological and Pathological Roles of NTSR2 in Several Organs and Diseases (Review) - Yang, Yuting; Zhang, Wenxin; Wei, Kun; Hu, Fei; Wu, Song; Ma, Yuan; Ouyang, Qing (Protein and Peptide Letters, 2024)
Neurotensin (NTS) and its receptors (NTSRs) have long been the subject of study and have shown to have a vital function in a variety of systems. They are specifically implicated in the development of tumors and have both oncogenic and anti-apoptotic effects. Neurotensin receptor 2 (NTSR2), like NTSR1, belongs to the G protein-coupled receptor family and has been linked to analgesia, mental disorders, and hematological cancers. However, several research reports have revealed that it exists in numerous different systems. As a result, it seems to be an extremely promising therapeutic target for a variety of diseases. As NTSR2 is particularly prevalent in the brain and has different distribution and developmental characteristics from NTSR1, it may play a specific role in the nervous system. The present review summarizes the expression and function of NTSR2 in different systems, to highlight its potential as a diagnostic tool or therapeutic target.
Keywords: physiological function